2016
DOI: 10.1210/en.2015-2050
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid-Induced Attenuation of the Inflammatory Response in Zebrafish

Abstract: Glucocorticoids are steroid hormones that are secreted upon stress. Their effects are mediated by the glucocorticoid receptor, which acts as a transcription factor. Because the antiinflammatory activity of glucocorticoids has been well established, they are widely used clinically to treat many inflammatory and immune-related diseases. However, the exact specificity, mechanisms, and level of regulation of different inflammatory pathways have not been fully elucidated. In the present study, a tail fin amputation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
57
3

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 74 publications
12
57
3
Order By: Relevance
“…In agreement with results obtained by Chatzopoulou and coworkers 2 with a tail fin amputation assay, the challenge with DSS induced a pro-inflammatory reaction with enhanced transactivation of the genes encoding the cytokines Il1β, Il8 and Il6 and the metalloproteinase Mmp-13, involved in inflammatory processes, in both WT and gr s357/s357 larvae, but not in the gr −/− strain. Subsequent treatment with DEX significantly depressed the transcription of the above genes, whereas no change was observed in the gr −/− strain.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In agreement with results obtained by Chatzopoulou and coworkers 2 with a tail fin amputation assay, the challenge with DSS induced a pro-inflammatory reaction with enhanced transactivation of the genes encoding the cytokines Il1β, Il8 and Il6 and the metalloproteinase Mmp-13, involved in inflammatory processes, in both WT and gr s357/s357 larvae, but not in the gr −/− strain. Subsequent treatment with DEX significantly depressed the transcription of the above genes, whereas no change was observed in the gr −/− strain.…”
Section: Discussionsupporting
confidence: 91%
“…Analysis of mmp - 9 , a metalloproteinase gene known to be down-regulated by GCs 2,28,29 , showed a statistically significant reduction of its expression after DEX in gr +/+ and gr s357 / s357 line, but not in gr −/− , in agreement with the loss of non-canonical, GRE-independent activity.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Similar effects are seen in glial cells and with the corticosteroid drug dexamethasone in human blood monocytes [41, 42]. Abrogation of inflammatory response by glucocorticoids is also observed in zebrafish in response to stress caused by tail vein amputation along with decrease in leukotriene B4 (LTB4) synthesis, an effect that is also seen upon treatment with the synthetic glucocorticoid beclomethasone [43]. Proteasome and eicosanoid profiling of human fibroblasts show that inflammation upregulates a number of eicosanoids synthesized by COX and LOX, such as PGE1, PGE2, TXB2, 11-HETE, and 12-HETE.…”
Section: Stress and Metabolismmentioning
confidence: 87%
“…Administration of the antidepressant fluoxetine as well as social interactions were shown to restore normal behavior [75,77]. Using this mutant, it was demonstrated that Gr mediates the glucocorticoid-induced inhibition of leukocyte migration upon wounding [78] and the stimulation of the formation of hematopoietic stem and progenitor cells (HSPCs) by glucocorticoids [79]. In addition, it was found that light adaptation in the retina was disturbed in mutant larvae [80].…”
Section: The Zebrafish Grmentioning
confidence: 99%